The Bishops in Ignatius of Antioch: Dominant Social Frame of Christian Collective Memory - Rivas Rebaque, Fernando (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
In the writings of Ignatius of Antioch we find that bishops occupy a dominant role in the life of the Christian community. Less than forty years before, they certainly had much lesser importance. How did this evolution happen? This article seeks to give an answer, using categories from the Sociology of Knowledge, focusing on the role of the bishops as the social framework which configured the collective memory of Christianity at the end of the First Century.